2010
DOI: 10.1016/j.joca.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular markers for articular cartilage

Abstract: Taken together, these results provide important novel insights into chondrocyte biology in general and AC in particular. In addition, it is reasonable to speculate, that some of the identified genes play distinct roles in the regulation of articular chondrocyte differentiation and/or function, thereby raising the possibility that they may serve as targets for non-operative therapies of osteoarthritis (OA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Previous gene profiling studies also showed higher expressions of these factors including Dkk3, Wif1, Sfrp5, Igfbp4/5, Nov, Gdf10, Grem1 and Frzb in articular chondrocytes than growth plate chondrocytes (9,13,18). We speculate that it may be more appropriate to use these signaling molecules in tissue engineering of articular cartilage because the articular chondrocytes under their physiological conditions in vivo are exposed to these factors and therefore may respond to them more optimally.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous gene profiling studies also showed higher expressions of these factors including Dkk3, Wif1, Sfrp5, Igfbp4/5, Nov, Gdf10, Grem1 and Frzb in articular chondrocytes than growth plate chondrocytes (9,13,18). We speculate that it may be more appropriate to use these signaling molecules in tissue engineering of articular cartilage because the articular chondrocytes under their physiological conditions in vivo are exposed to these factors and therefore may respond to them more optimally.…”
Section: Discussionmentioning
confidence: 58%
“…Esm1 has been reported to be secreted mainly by endothelial cells of organs like lung or kidney and to function as a regulator of cell adhesion, inflammatory disorders, and tumor progression (19,20). Similarly, Thbs4 is another extracellular matrix protein holding promise for the study of the role of articular cartilage integrity in the 16 selected genes because Thbs4 was also reported to show the highest specificity for articular cartilage expression in a previous RT-PCR screening (18). In fact, most of the other thrombospon- A, effects of rhFGF18 on mRNA levels of Mmp, Adamts, and Timp family genes after 3-day culture of mouse femoral heads (2 g/ml rhFGF18) and 1-day culture of mouse articular chondrocytes (250 ng/ml rhFGF18).…”
Section: Discussionmentioning
confidence: 99%
“…n-3 PUFAs inhibit these pathways directly through ligand-mediated activation of GPR120 and downstream inactivation of transforming growth factor-β activated kinase 1 (TAK1) 13 . Chondrocytes express GPR120 39 , but the physiological relevance of GPR120-mediated inactivation of TAK1 in articular chondrocytes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Development and grading of OA is mainly determined by histological analyses [4,6,14]. In humans, grade and prevalence of OA may be detected by MRI scanning [15,16] and through X-ray examination [17]. Thus, correlation of histological changes and MRI scanning is needed in diagnosis of OA.…”
Section: Introductionmentioning
confidence: 99%
“…The pig and notably the Göttingen Minipig (GM) is often used in articular cartilage research [5,17,23,24] and is also a common model for the study of regeneration of focal cartilage defects [7,25,26] but the transection of the ACL has rarely been performed in this species up to now [6]. For the articular cartilage research skeletal mature individuals are required as older pigs may mirror the human condition better, as OA is mostly an affliction of older people whether or not there were previous injuries [27,28].…”
Section: Introductionmentioning
confidence: 99%